MiR-944/CISH mediated inflammation via STAT3 is involved in oral cancer malignance by cigarette smoking - Hsuan-Yu Peng; Jenn-Ren Hsiao; Sung-Tau Chou; Yuan-Ming Hsu; Guan-Hsun Wu; Yi-Shing Shieh; Shine-Gwo Shiah (Neoplasia: An International Journal for Oncology Research, 2020)
The cytokine-inducible Src homology 2-containing protein (CISH) is an endogenous suppressors of signal transduction and activator of transcription (STAT) and acts as a key negative regulator of inflammatory cytokine responses. Downregulation of CISH has been reported to associate with increased activation of STAT and enhanced inflammatory pathways. However, whether microRNAs (miRNAs) play a crucial role in CISH/STAT regulation in oral squamous cell carcinoma (OSCC) remains unknown. The expression of CISH on OSCC patients was determine by quantitative real-time PCR (qRT-PCR) and immunohistochemistry. Specific targeting by miRNAs was determined by software prediction, luciferase reporter assay, and correlation with target protein expression. The functions of miR-944 and CISH were accessed by transwell migration and invasion analyses using gain- and loss-of-function approaches. Enzyme-linked immunosorbent assay (ELISA) and qRT-PCR were used to evaluate the pro-inflammation cytokines expression under the miR-944, CISH, NNK or combinations treatment. We found that the CISH protein, which modulates STAT3 activity, as a direct target of miR-944. CISH protein was significantly down-regulated in OSCC patients and cell lines and its level was inversely correlated with miR-944 expression. The miR-944-induced STAT3 phosphorylation, pro-inflammation cytokines secretion, migration and invasion were abolished by CISH restoration, suggesting that the oncogenic activity of miR-944 is CISH dependent. Furthermore, tobacco extract (NNK) may contribute to miR-944 induction and STAT3 activation. Antagomir-mediated inactivation of miR-944 prevented the NNK-induced STAT3 phosphorylation and pro-inflammation cytokines secretion. Altogether, these data demonstrate that NNK-induced miR944 expression plays an important role in CISH/STAT3-mediated inflammatory response and activation of tumor malignancy.